2021
DOI: 10.1007/s10238-021-00682-3
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells therapy in acute myocardial infarction: a new era?

Abstract: Stem cells transplantation after acute myocardial infarction (AMI) has been claimed to restore cardiac function. However, this therapy is still restricted to experimental studies and clinical trials. Early un-blinded studies suggested a benefit from stem cell therapy following AMI. More recent blinded randomized trials have produced mixed results and, notably, the last largest pan-European clinical trial showed the inconclusive results. Furthermore, mechanisms of potential benefit remain uncertain. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…In most stem cell-treated AMI trials, transplanted cells were BMNCs and the benefits in cardiac regeneration were mixed and uncertain ( 10 ). To date, the autologous bone marrow cell therapy in AMI trial (BAMI) is the largest study of stem-based cell therapy for AMI in the world.…”
Section: Discussionmentioning
confidence: 99%
“…In most stem cell-treated AMI trials, transplanted cells were BMNCs and the benefits in cardiac regeneration were mixed and uncertain ( 10 ). To date, the autologous bone marrow cell therapy in AMI trial (BAMI) is the largest study of stem-based cell therapy for AMI in the world.…”
Section: Discussionmentioning
confidence: 99%
“…Cells of extracardiac origin were shown to home to the injured myocardium and contribute to repair via an effect on angiogenesis and inflammation [2,3]. Seeing this potential marked the onset of the quest for CVD cell-based therapy, which has shown to have some beneficial effects [2,3,5,6 ▪▪ ,7 ▪▪ ]. Yet, it depends on both cell type and the extent of cell retention and survival.…”
Section: Cell-based Therapiesmentioning
confidence: 99%
“…PreSERVE-AMI found an effect only upon adjustment for ischemia time [5]. The MI cell-based therapy therefore does not seem to be thoroughly convincing, and the pros and cons are summarized elsewhere [6 ▪▪ ]. Optimization steps such as cell preconditioning or genetic modifications are being studied to enhance cell properties (reviewed in [7 ▪▪ ]).…”
Section: Cell-based Therapiesmentioning
confidence: 99%
“…Stem cell therapy in patients with AMI was introduced as putative treatment in repairing the damaged myocardium. So far, multipotent stem cells from different sources, such as bone marrow-derived stem cells, circulating progenitor cells, and mesenchymal cells, have been employed for transplantation which can be delivered through different routes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that cell therapy of the infarcted myocardium can promote regeneration of the cardiomyocytes and angiogenic capacity by producing different paracrine factors [ 5 ]. Among different kinds of cells, bone marrow mononuclear cells (BM-MNCs) and mesenchymal stem cells (MSCs) are the most frequently explored stem cells in trials exploring the potential regenerative effects of stem cells on injured myocardial tissue in AMI patients [ 4 ]. Autologous administration of stem cells in humans for assessing their effects on cardiac function in AMI was first appeared in a study at 2001 by Strauer et al which showed improvement in ejection fraction (LVEF) and reduction in scar size [ 6 ].…”
Section: Introductionmentioning
confidence: 99%